Unsafe spaces : ending sexual abuse in universities - Tutchell, Eva; Edmonds, John (Emerald Publishing Limited, 2020)
Unsafe Spaces reveals the shocking extent of sexual abuse in English and Welsh universities. Thousands of students and staff suffer sexual abuse every year and too little is being done to end what has become a public scandal. This important book is based on research, a detailed examination of current practice and on the compelling testimony of survivors, who tell of their ordeal and the miserable after-effects. Confidence is shattered and careers are damaged. Unsafe Spaces names the handful of universities who have approached this problem with sympathy and professionalism, but finds that the majority are failing their students and staff. Usually sexual abuse is given too little attention, and most universities have not even collected reliable information or recruited trained specialists. Too often, universities seek to conceal the extent of sexual misconduct instead of focusing on care and prevention. The authors advocate greater openness and a new policy agenda, making the safety and welfare of everyone on campus into a top priority for university management. Crucial reading for university leaders, staff, students, and those committed to ending sexual violence, Unsafe Spaces offers practical solutions both to the present crisis and to the culture of disrespect which blights many universities and allows sexual abuse to continue unchecked.